A comparative study of disinfectants for cleaning intensive care unit surfaces - Eman Muftah Elzouki; Najah Ahmeda Ibrahim; Salwa Muftah Eljamay (African Journal of Advanced Pure and Applied Sciences, 2022)
Disinfection plays a major role in preventing these infections. Aim: treating nosocomial infections is challenging as most of the causative agents are multi-drug resistant. Material &Method: In this context, an attempt was made to compare the efficacy of (5%, 10%) sodium hypochlorite disinfectant and (70%) isopropyl alcohol as surface disinfectants in the Intensive Care Unit (ICU). Samples were collected from bed railings, the surface of the monitor and the side table of all ICUs of Al Wahda Hospital. Samples were collected before and after disinfection using appropriate disinfectants. After cleaning samples were collected after a contact time of 20 minutes. Samples were inoculated onto one set of the blood agar plates and one set of MacConkey agar plates incubated at 37◦C under aerobic conditions. After incubation colony count was done manually to compare the results. Result: Under aerobic conditions the 10% sod. Hydrochloride was found 96.7% more efficient than isopropyl alcohol and when used 70%isopropyl alcohol was found only 36.7%. This difference is significant statistically as the p-value is 0.05. 10% sod, Hydrochloride is a better surface disinfectant to be used in intensive care units as it is safe to use and cost-effective on the other hand isopropyl alcohol is less efficient and also it is expensive. Conclusion: This study showed that there were statistically significant differences between the efficacies of disinfectants. that 110% sodium hypochloride is a better surface disinfectant to be used in intensive care units as it is safe to use and cost-effective